Superhydrophobic Biological Fluid‐Repellent Surfaces: Mechanisms and Applications. Issue 12 (26th October 2022) - Luo, Jing; Yu, Huali; Lu, Binyang; Wang, Dehui; Deng, Xu
Abstract: Superhydrophobic biological fluid‐repellent surfaces (SBFRSs) have attracted great attention in the treatment of blood and urine‐related diseases because of their unique wettability and compatibility, which creates a new path for the development of medical apparatus and instruments, and are expected to create advances in various fields. Here, this review provides an up‐to‐date summary of research progress on the repellent mechanism and application of SBFRSs. The underlying physical and chemical principles for designing superhydrophobic surfaces are first introduced. Then, the dialectical influences of solid‐liquid interactions between superhydrophobic surfaces and biological fluids on the wettability and compatibility are emphatically expounded. Subsequently, attention is drawn to the recent applications of SBFRSs in biomedical fields, such as surgical medical apparatus, implant materials, extracorporeal circulation devices, and biological fluid detection. Finally, the outlook and challenges in terms of employing SBFRSs are also discussed. This review is expected to provide a comprehensive guidance for the preparation of SBFRSs with compatibility and long‐term superhydrophobic stability that is closely related to clinical applications. Abstract : Superhydrophobic biological fluid‐repellent surfaces (SBFRSs) are widely used in the biomedical field because of their wettability and compatibility. In this review, recent progress applying SBFRSs from the perspectives of physical and chemical principles, solid‐liquid interface interactions, and biomedical field applications are summarized, providing a comprehensive guidance for the design of SBFRSs.